Investment analysis and sustainable finance: A bibliometric study of real options as a financial tool for the viability of geothermal renewable energy - Becker, Michel; Lacerda, Rogerio; Lima, Marcus Vinicius Andrade de (Seven Editora, 2023)
Introduction: The finance/investment and Renewable Energy (RE) sectors are central to any climate change programme. The first has been identified as fundamental to the advancement of the zero-carbon energy transition, acting as a facilitator and catalyst determining this climate economic transformation (Chenet et al., 2019). The second, is the main component of any climate change mitigation strategy (aren't et al., 2011) and its associated technologies have been the target of increasing interest, becoming a reality in recent years (Dranka et al., 2020).Research Problem and Objective: Financial assessments hinder the development of geothermal energy (Lukawski et al., 2016) and the real-option approach could contribute to its development (Compernolle et al., 2019; Fernandes et al., 2011). Thus, it is opportune to answer: How can the approach of real options contribute to the analysis of investments in geothermal plants? The article aims to expand the understanding of investments and real options in geothermal plants, especially by: i. Select bibliographic ref. on the subject; ii. Perform bibliometric analyses on the articles and their references.Theoretical Basis: Real options theory is known to increase the value of projects under uncertainty by modeling their flexibility in response to changes in their environments. It could be used to address current environmental and energy issues by increasing the value of electricity generation projects, especially renewable energy projects (Martínez Ceseña et al., 2013). Geothermal energy is a renewable source, derived from the thermal energy stored in the Earth's interior. Its production has a low carbon footprint and the ability to provide continuous energy and heat (Compernolle et al., 2019).Methodology: The structured process was used for the selection and analysis of the ProKnow-C scientific literature (Ensslin et al., 2017). Once the Scopus and WoS databases were defined, as well as the research axes, investment analysis and renewable energy axes, articles were searched for in the databases, which systematically passed through filters of scientific recognition, alignment to the research and adherence to the proposed theme and resulted in a Bibliographic Portfolio (PB) that subsidized the bibliometric analyses.Analysis of Results: As a result of the methodological process, a bibliographic portfolio was formed consisting of 25 articles, aligned with the objective of the research, adhering to the proposed theme and with scientific recognition. In the bibliometric analyses, graphs were elaborated to adequately represent the quantitative  and cognitive aspects of the research, whose observable parameters are: Featured articles, their references, featured authors, number of citations, keywords and most relevant journals.Conclusion: This research aimed to present a relevant theoretical bibliographic portfolio, detailing the process that resulted in 25 articles. In the bibliometric analyses, it was evidenced: a) that the highlighted journals were Energy Policy, Energy Economics and Renewable and Sustainable Energy Reviews; b) as authors the researcher Ferreira, P. was the only one who participated with 3 papers in the selected PB and Fleten S. E. had more than 10 works composing the references of the PB; and c) the articles (Boomsma et al., 2012) and (Fernandes et al., 2011) stood out in the classification of academic relevance. DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-130